Inter Linkages among Agriculture, Manufacturing and Service Sectors: Empirical Evidence from Sri Lanka’s Provincial Economies - Sooriyakumar, K.; Poonkulaly, S.; Sireeranhan, A. (University of Jaffna, 2015)
This study examines the relationships among agriculture, manufacturing and service sectors of Sri Lanka’s provinces. Annual data from 2000 to 2013 for nine provinces of Sri Lanka were used to develop a Panel Vector Error Correction Model for this study. The results of this study show that there is a positive relationship between the agricultural sector and manufacturing sector. The impact of agricultural growth on manufacturing growth is about three times of the impact of manufacturing growth on agricultural growth. The negative relationship between the agricultural sector and service sector means that these two sectors competes each other for labor and capital goods. Manufacturing and service sector contribute each other for their growth. These findings would help policy makers in central government and local governments of all provinces formulate the sound policies to accelerate the economic development in all provinces.
Keywords: Economic Growth; Panel Vector Error Correction Model; Regional Economics